PENGARUH PEMBERIAN SARI KACANG HIJAU (VIGNA RADIATE) TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU NIFAS - Naimah Nasution (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2022)
Abstrack Exclusive breastfeeding is breastfeeding only for infants aged 0-6 months without providing additional food or other liquids such as formula milk, oranges, honey and tea water. In addition, additional food is also not recommended either in solid or liquid form. This study was to determine the effect of giving green bean juice (Vigna Radiate) to the increase in breast milk production in postpartum mothers at the Yeni Clinic, Tinggi Raja District, Asahan Regency in 2022. This type of research is quantitative with the design used in this study is a quasi-experimental design (Quasy Experiment) using pre and post test One Group design. Analysis of the data used is the Paired T-test. What was carried out on 10 postpartum mothers who experienced problems in exclusive breastfeeding at the Yeni Clinic, which was held in June 2022. It can be seen that those who have a score of breast milk production before being given Green Bean Extract who have a score of less than 9 people (90%), a sufficient score of 1 person (10%), and breast milk production after being given Green Bean Extract which has a production score 2 people (20%), enough breast milk production scores 8 people (80%). Based on the results of the study, the p-value is 0.000 <0.005, so it can be assumed that there is an effect of giving Green Bean Juice (vigna radiation) to the increase in breast milk production in postpartum mothers at the Yeni Clinic, Tinggi Raja District, Asahan Regency in 2022.